Client Centered Counseling To Handle Anxiety Of Indoor Hockey Athletes Club Hockey Tower Kudus, Is It Effective? - Febriyanti, Ita; Azmi, Khilman Rofi; Ulya, Rifqi Minchatul (Konseling Edukasi : Journal of Guidance and Counseling, 2025)
This study describes how much influence client-centered counseling has on the anxiety of Menara Hockey Club Kudus indoor hockey athletes. Anxiety is the emergence of an individual's emotional state experiencing stress, as well as signs of feeling tense, restless thoughts, and certain body responses. The purpose of this study 1) to determine the anxiety experienced by athletes before receiving client centered counseling services; 2) to determine how effective client centered counseling services are in reducing athlete anxiety. This research method uses quantitative experiments. There are four athletes from forty MHC Kudus athletes taken using purposive sampling. Data analysis using SPSS. The results showed that four athletes experienced high levels of anxiety before the service, 100%, and after being given the service the results were one athlete getting very low 25%, and three athletes getting low anxiety 75%. The T test results show the value of t = 17.554 and the value of p = 0.000 (p <0.05). It is understood that client-centered counseling has an impact on reducing the anxiety experienced by Menara Hockey Club Kudus indoor hockey athletes. Keywords: Client centered counseling; anxiety; athletes.